PENGARUH FAKTOR KEPRIBADIAN INDIVIDUAL, SELFF-EFFICACY SERTA LOCUS OF CONTROL TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH DI KECAMATAN CARINGIN KABUPATEN BOGOR - Ujang Sumantri; Dwi Gemina (Fakultas Ekonomi Universitas Djuanda, 2015)
Sector of micro, small and medium-sized enterprises (UMKM) substance in the Indonesian economy contribute fairly important, not only in terms of profitability and constructive in improving the welfare of society, but also in terms of its role in employment (human resources). The research objectives: 1) to analyze the influence of individual personality factors, self-efficacy and locus of control simultaneously on the performance UMKM; 2) analyze the influence of individual personality, self-efficacy, and locus of control partially on the performance of UMKM; 3) what factors inhibiting and driving on the performance SME. The object of this research is 30 UMKM flagship product of questionnaires as much as 60 questioner with descriptive research methods and verification. Tests conducted are validity, reliability and classical assumptions as well as the size of the Likert scale for multiple linear regression. Results of research simultaneously and partially individual personality factors, self-efficacy and locus of control influence on the performance of SME. Supporting factors for superior product performance of UMKM Caringin District of Bogor Regency is the individual personality factors, self-efficacy and locus of control.Keywords: Individual Personality Factors, Self-Efficacy, Locus of Control and Performance UMKM